Evaluating Indonesia’s Elementary School Admission Policy Using the CIPP Model: A Case Study in Central Tapanuli - Winda Winastri Siregar; Dadan Suryana; Nuhafizah Nurhafizah; Nenny Mahyuddin (AL-ISHLAH: Jurnal Pendidikan, 2025)
The New Student Admission policy (Penerimaan Peserta Didik Baru / PPDB) is intended to promote equitable, transparent, and accountable access to basic education in Indonesia. However, its implementation at the elementary level, particularly in rural contexts, remains uneven and underexplored. This study evaluated the implementation of PPDB in three public elementary schools in Sibabangun District, Central Tapanuli Regency, using the Context, Input, Process, Product (CIPP) evaluation model. A mixed-methods approach with a sequential explanatory design was employed. Quantitative data were collected through structured questionnaires administered to school principals and teachers, while qualitative data were obtained through semi-structured interviews and document analysis. Descriptive statistics and thematic analysis were used to analyze the data. The findings indicate that, in the context dimension, PPDB implementation aligns with policy objectives but requires stronger collaboration with private schools to optimize zoning-based admissions. In the input dimension, human resources, facilities, and implementation mechanisms are generally adequate. The process dimension reveals partial compliance with established procedures, with challenges related to schedule adherence and unmet enrollment targets. In the product dimension, PPDB implementation reflects the principles of objectivity, transparency, accountability, and fairness, although enrollment outcomes remain suboptimal. These findings highlight the need for continuous evaluation, improved inter-school coordination, and context-sensitive implementation strategies to enhance the effectiveness of PPDB in rural elementary school settings.